DESIGNING A STRATEGY MAP BASED ON BALANCE SCORECARD IN PERUMDA TIRTA SILAU PIASA ASAHAN DISTRICT - Gita Putri Desiana Daulay; Abdul Rahim Matondang; Nazaruddin (RADJA PUBLIKA, 2024)
Research conducted at Perumda Tirta Silaupiasa, Asahan Regency aimed at designing a strategy map based on a balanced scorecard, because the company was still unable to achieve targets and align with the company's vision and mission. This research uses descriptive qualitative methods. Primary data was collected through interviews and secondary data was obtained through company documents and related literature. The results of research at Perumda Tirta Silaupiasa, Asahan Regency, the vision and mission are effective, but they still do not include the values ​​adhered to by the company. SWOT analysis which shows the company's strengths, weaknesses, opportunities and threats produces 13 strategic targets which are classified into four balanced scorecard perspectives, namely, 3 strategic targets from a financial perspective, 6 strategic targets from a customer perspective, 2 strategic targets from an internal business process perspective and 2 strategic targets strategy on a learning and growth perspective. Then, the strategy targets are displayed in the form of a strategy map.